Optimal Design of a High-altitude Solar-Powered Unmanned Airplane - Bento Silva de Mattos; Ney Rafael Secco; Eduardo Francisco Salles (Journal of Aerospace Technology and Management, 2013)
http://dx.doi.org/10.5028/jatm.v5i3.223